ANALYSIS ON RUB IMPACT NON-LINEAR RESPONSE OF THE COUNTER-ROTATING DUAL-ROTOR SYSTEM - SUN Tao; QIN WeiYang; XIANG Huan (Jixie qiangdu)
In this paper, we investigated the rub-impact in the counter-rotating dual-rotor system. First we discretized the model of the counter-rotating rotor system and derived its FEM dynamical equations. Then we studied the rub impact fault caused by the sudden imbalance at the outer rotor and its influence on the response. The Wilson-θ method and other methods were employed to solve the equations. It can be seen that with the variation of rotating speed the Hopf bifurcation will occur. The quasi-periodic response exhibits tori twist in the Poincare section. It is found there exists a route to chaos where the quasi-periodic tori intersect each other gradually.